The Impact of Tourism on Local Economic Development in Batu (CaseStudy: Jatim Park 2 Area) - Sofhia Dwi Febriani (Jurnal Ilmiah Mahasiswa FEB, 2015)
Batu has tourism potential which benefits its  economic development. The potentials ranges from the available natural and man-made tourist and cultural attractions. As one of the cities with the brand image of travel, tourism potential in Batu is strong enough to attract   tourist visits which of course helps the economic development processThis study aims to determine the impact of the tourism sector on the Local Economic Development (LED) in Batu, especially around tourist area around Jatim Park 2. The data were obtained through interviews, documentation, observation, and additional info taken from the official website. By using a phenomenological approach, the research results show that the   Tourism in Jatim Park 2 Region gives significant impact  on Local Economic Development in Batu. The impacts include the following sector (1) The development of the informal sector, (2) Employment, (3) Welfare (personal wages and salaries), and (4) Empowerment. To maximize the synergies between the tour manager, government,  and community is one of the  solutions that can be used to further develop  the tourist areas, which certainly can have a big impact on the quality of life of local people there , especially those who are  directly involved in the world of SMEs. Maximizing the formation institutions of local communities to participate in activities or certain  meeting regarding  the needs of tourist attractions   is one of the alternatives that could be used to maximize the presence of the tourist area. Keyword : Tourism, Local Economic Development (LED), Tourism Impact